Strategi Perbatasan Suku Dayak Agabag dalam pemenuhan Hak Budaya di Ulu Sembakung, Kalimantan Utara - Puji Hastuti (Jurnal HAM, 2024)
The local elites of the Dayak Agabag community are acutely aware of their minority status, which paradoxically presents them with unique opportunities. Situated as a frontier people within Indonesia, the Dayak Agabag have cultivated strong social bonds with the Murut Pensiangan community in Malaysia, fostering cultural cohesion that transcends national borders. These sociocultural ties, while beneficial for community solidarity, are viewed as a challenge to state sovereignty and nationalistic ideals. Ironically, local elites of the Agabag community have adeptly utilized their minority status to advocate for the development of modern-state infrastructure in their region. This article critically examines the cultural rights challenges confronting the Dayak Agabag along the Indonesia-Malaysia border, with a focus on the political agency of their local elites in shaping affirmative policies for marginalized communities and advocating for human rights. It sheds light on how both elite and community movements seek legitimacy in their endeavors. Through an ethnographic lens, the study reveals that Dayak Agabag's local elites have strategically asserted their political agency to carve out autonomy in countering state spatial domination and advocating for human rights as frontier people. Central to this analysis is the understanding that the political agency of Dayak Agabag's local elites enables them to maintain their minority status effectively, leveraging it to access political advantages and privileges across national borders. This agency offers valuable insights into how marginalized frontier communities can harness their indigenous political power to secure cultural rights, navigate cross-border dynamics, and maintain social legitimacy despite facing formal legal challenges. In conclusion, this article underscores the nuanced strategies employed by Dayak Agabag's local elites to navigate their geopolitical context, advocating for rights and infrastructure development while managing complex transnational relationships. It highlights the resilience and adaptability of frontier communities in utilizing their indigeneity to negotiate and assert their place in contemporary political landscapes.